Is there a role for IGF‐1 in the development of second primary cancers?. (13th October 2016) - Shanmugalingam, Thurkaa; Bosco, Cecilia; Ridley, Anne J.; Van Hemelrijck, Mieke
Abstract: Cancer survival rates are increasing, and as a result, more cancer survivors are exposed to the risk of developing a second primary cancer (SPC). It has been hypothesized that one of the underlying mechanisms for this risk could be mediated by variations in insulin‐like growth factor‐1 (IGF‐1). This review summarizes the current epidemiological evidence to identify whether IGF‐1 plays a role in the development of SPCs. IGF‐1 is known to promote cancer development by inhibiting apoptosis and stimulating cell proliferation. Epidemiological studies have reported a positive association between circulating IGF‐1 levels and various primary cancers, such as breast, colorectal, and prostate cancer. The role of IGF‐1 in increasing SPC risk has been explored less. Nonetheless, several experimental studies have observed a deregulation of the IGF‐1 pathway, which may explain the association between IGF‐1 and SPCs. Thus, measuring serum IGF‐1 may serve as a useful marker in assessing the risk of SPCs, and therefore, more translational experimental and epidemiological studies are needed to further disentangle the role of IGF‐1 in the development of specific SPCs. Abstract : The insulin‐like growth factor (IGF) family plays an important role in the development of cancer. Epidemiological studies have reported a positive association between circulating IGF‐1 levels and various primary cancers.